Gas and aerosol emissions from Villarrica volcano, Chile - Sawyer, G; Salerno, G; Le Blond, J; Martin, R; Spampinato, L; Roberts, T; Mather, T; Witt, M; Tsanev, V; Oppenheimer, C (2011)
Here we report results from a multidisciplinary field campaign at Villarrica volcano, Chile, in March 2009. A range of direct sampling and remote sensing techniques was employed to assess gas and aerosol emissions from the volcano, and extend the time series of measurements that have been made during recent years. Airborne traverses beneath the plume with an ultraviolet spectrometer yielded an average SO2 flux of 3.7kg s-1. This value is similar to previous measurements made at Villarrica during periods of quiescent activity. The composition of the plume was measured at the crater rim using electrochemical sensors and, for the first time, open-path Fourier transform infrared spectroscopy, yielding a composition of 90.5mol% H2O, 5.7% CO2, 2.6% SO2, 0.9% HCl, 0.3% HF and <0.01% H2S. Comparison with previous gas measurements made between 2000 and 2004 shows a correlation between increased SO2/HCl ratios and periods of increased activity. Base-treated filter packs were also employed during our campaign, yielding molar ratios of HBr/SO2=1.1×10-4, HI/SO2=1.4×10-5 and HNO3/SO2=1.1×10-3 in the gas phase. Our data represent the most comprehensive gas inventory at Villarrica to date, and the first evaluation of HBr and HI emissions from a South American volcano. Sun photometry of the plume showed the near-source aerosol size distributions were bimodal with maxima at <0.1 and ~1-m. These findings are consistent with results from analyses in 2003. Electron microscope analysis of particulate matter collected on filters showed an abundance of spherical micron-sized particles that are rich in Si, Mg and Al. Non-spherical, S-rich particles were also observed. © 2011 Elsevier B.V.